2011
DOI: 10.1111/j.1365-2524.2011.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of older adults’ awareness of community support services in Hamilton, Ontario

Abstract: Community support services (CSSs) have been developed in Canada and other Western nations to enable persons coping with health or social issues to continue to live in the community. This study addresses the extent to which awareness of CSSs is structured by the social determinants of health. In a telephone interview conducted in February-March 2006, 1152 community-dwelling older adults (response rate 12.4%) from Hamilton, Ontario, Canada were made to read a series of four vignettes and were asked whether they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Across the four vignettes, 43 per cent of respondents were unable to name even one CSS (Tindale et al, 2011). Older adults were more likely to be aware of services to assist with caregiver burden, dementia services, and transportation services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Across the four vignettes, 43 per cent of respondents were unable to name even one CSS (Tindale et al, 2011). Older adults were more likely to be aware of services to assist with caregiver burden, dementia services, and transportation services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The finding that health information resources have significant impacts on awareness of the project is consistent with the results of previous studies. 19 31 In particular, the observation that PWD who receive information from health service centers (e.g., clinics, hospitals, and public health centers) were more likely to be aware of the project is supported by the previous finding that most PWD who utilized the project were referred by a physician. 14 Furthermore, in the 2020 Survey on Persons with Disabilities conducted by the Ministry of Health and Welfare, mass media was the second most common source of healthcare information among PWD; thus, it may be effective to use mass media (in addition to health service centers) when promoting the project.…”
Section: Discussionmentioning
confidence: 83%
“…Though we selected most of the independent variables according to the Andersen’s model, 17 19 21 22 23 24 25 some variables added to the model through the review of the prior studies about the health service demand or awareness or unmet need for healthcare. 1 2 26 28 29 30 31 32 For example, predisposing factors included socioeconomic characteristics such as age (< 20 years, 20–64 years, and ≥ 65 years), gender, marital status, education level, and living arrangement (e.g., living alone). Enabling factors included income level, occupational status, type of public health insurance, presence of caregivers (including informal caregivers such as family members and formal caregivers such as activity assistants), and homebound status (going out less than once per week and needing help from others for most activities of daily living [ADL]).…”
Section: Methodsmentioning
confidence: 99%
“…For example, working with lead agencies would make it possible to host joint team meetings to discuss referrals, service gaps, cancellations of service, and further supports that may be needed to support tenants (Sheppard, Gould, et al, 2022). Finally, previous research shows that the biggest barrier to accessing community support services is lack of awareness (e.g., Calsyn & Roades, 1993;Denton et al, 2008Denton et al, , 2010Strain & Blandford, 2002;Tindale et al, 2011); and there are several opportunities that social housing providers can take to enhance awareness. For example, through partnerships with community support service agencies, buildings could host education sessions to teach tenants about the different supports that are available and the kinds of needs that those services can help with.…”
Section: Recommendations To Increase Access To Servicesmentioning
confidence: 99%
“…Community Support Service Use Among Older Adults Although most community-dwelling older adults reported that they would seek help from a community support service agency if needed (Denton et al, 2008;Tindale et al, 2011), there are generally low utilization rates of their services. For example, Lehning, Kim, and Dunkle (2013) reported in their sample of 1,099 black older adults that only 14.9 per cent accessed functional support services (such as home-delivered meals and homemaking services), 18.9 per cent used home repair and home maintenance services, and 46.6 per cent accessed out-of-home services such as senior centres, congregate dining, and transportation.…”
Section: Introductionmentioning
confidence: 99%